1986
DOI: 10.1002/macp.1986.021870415
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizable phospholipids and their polymeric liposomes

Abstract: Phospholipids containing polymerizable itaconate moieties were synthesized and their formation of liposomes was studied. Although the itaconate phospholipids alone form rather unstable liposomes by ultrasonication, mixtures with other phospholipids such as dipalmitoyl phosphatidylcholine, bis(2,4-octadienoyl) phosphatidylcholine or cholesterol, form stable and single-wall, small sized liposomes. The polymerizability of itaconate phospholipids and the stabilization of such mixed liposomes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The polymerizable moiety "itaconate (-OCO-CH2-C( = CHJ-COO-)" belongs to an intriguing system used in the stabilization of vesicles [53]. Ultraviolet irradiation seems to be the preferred method for photo-initiation of the itaconate moiety.…”
Section: Other Polymerizable Lipidsmentioning
confidence: 99%
“…The polymerizable moiety "itaconate (-OCO-CH2-C( = CHJ-COO-)" belongs to an intriguing system used in the stabilization of vesicles [53]. Ultraviolet irradiation seems to be the preferred method for photo-initiation of the itaconate moiety.…”
Section: Other Polymerizable Lipidsmentioning
confidence: 99%
“…An initial study of phospholipids containing itaconate as polymerizable moieties were reported by Takane et a1. 26 Polymerization of the sonicated suspension of the lipid/cholesterol (20/3) mixture was attempted with UV light from a high-pressure mercury lamp. Solubility of the polymers in chloroform indicates that the polymers were not long.…”
Section: -78mentioning
confidence: 99%
“…Various polymerizable lipids have been synthesized and polymerized as liposomes to investigate their stability. [3][4][5][6][7][8][9][10][11][12] We have mentioned the importance of the selection of proper polymerization methods in order to obtain stable liposomes.13,14 Since polymerized liposomes with phase transition like nonpolymerized liposomes are difficult to make, the polymerization of mixed liposomes containing both polymerizable and functional membrane constituents has been proposed. 15,16 In polymerized mixed liposome systems, polymerized regions are phase separated from monomeric regions because polymerization itself induces phase separation by the direct binding of polymerizable lipids through covalent bonds regardless of their affinities.…”
Section: Introductionmentioning
confidence: 99%